KREASI ANIMASI 2D UNTUK MENINGKATKAN BRAND AWARENESS PADA TOKO PERCETAKAN HIROPRINT - Anisya Mardiyanti; Edy Siswanto; Ahmad Ashifuddin Aqham; Dendy Kurniawan (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
Hiroprint Printing Shop is a business engaged in printing services, providing products such as stamps, business cards, banners, stickers, mugs, T-shirt screen printing, and visual design services. In the last two years, the average number of customers only reached 528 per year or 52.8% of the 1,000-customer target. This condition indicates low brand awareness, requiring a more effective promotional strategy. This study aims to create a 2D animation advertisement as a digital promotional medium to increase Hiroprint’s brand awareness. The research method used is Research and Development (R&D), consisting of planning, product development, and testing stages. The result of this study is a 2D animation advertising video featuring characters of customers, designers, finishing operators, and delivery staff to illustrate service quality and speed. The final product is a 2D animation video in HDTV 1080p, 24fps, mp4 format. This 2D animation-based promotional media is expected to increase customer interest, strengthen brand image, and help Hiroprint achieve its marketing targets.